Inwentarz kościoła parafialnego w Łunińcu z 1938 roku - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2013)
Each inventory which refers to the actual list of quantity and value of all the assets of the entity, in this case the St. Joseph parish church in Łuniniec in 1938, is the basis for evaluation of the financial status of this parish. It contains all the data on the parish church, its furniture, paraments and liturgical vessels. It describes the parish office, produced documents of this office and all financial inflows for the parish and clergy working in it. The inventory, like the documentation confirming the parish visitation, is very authoritative and rich in information not only on the very parish, but also on the people and the prevailing relations in the parish.